Nanoparticle conjugation of antigen enhances cytotoxic T-cell responses in pulmonary vaccination - Nembrini, Chiara (National Academy of Sciences, 2011)
The ability of vaccines to induce memory cytotoxic T-cell responses in the lung is crucial in stemming and treating pulmonary diseases caused by viruses and bacteria. However, most approaches to subunit vaccines produce primarily humoral and only to a lesser extent cellular immune responses. We developed a nanoparticle (NP)-based carrier that, upon delivery to the lung, specifically targets pulmonary dendritic cells, thus enhancing antigen uptake and transport to the draining lymph node; antigen coupling via a disulfide link promotes highly efficient cross-presentation after uptake, inducing potent protective mucosal and systemic CD8(+) T-cell immunity. Pulmonary immunization with NP-conjugated ovalbumin (NP-ova) with CpG induced a threefold enhancement of splenic antigen-specific CD8(+) T cells displaying increased CD107a expression and IFN-γ production compared with immunization with soluble (i.e., unconjugated) ova with CpG. This enhanced response was accompanied by a potent Th17 cytokine profile in CD4(+) T cells. After 50 d, NP-ova and CpG also led to substantial enhancements in memory CD8(+) T-cell effector functions. Importantly, pulmonary vaccination with NP-ova and CpG induced as much as 10-fold increased frequencies of antigen-specific effector CD8(+) T cells to the lung and completely protected mice from morbidity following influenza-ova infection. Here, we highlight recruitment to the lung of a long-lasting pool of protective effector memory cytotoxic T-cells by our disulfide-linked antigen-conjugated NP formulation. These results suggest the reduction-reversible NP system is a highly promising platform for vaccines specifically targeting intracellular pathogens infecting the lung.